Penerapan Multimedia Interaktif Wayang Golek Menggunakan Metode Multimedia Development Life Cycle (MDLC) Pada Tingkat Sekolah Dasar (SD) - Nashrullah, Muhammad Rikza; Noerkemalasari, Dylla (Jurnal Algoritma, 2025)
Wayang golek is one of Indonesia's traditional arts originating from West Java and plays an important role in Sundanese culture. However, along with the development of technology and information, the existence of wayang golek is threatened with extinction due to lack of support and public interest, especially among the younger generation. This study aims to increase students' interest and understanding of wayang golek through the application of interactive multimedia based on the Multimedia Development Life Cycle (MDLC). The MDLC method is used in the development of this interactive multimedia application, which includes the stages of Concept, Design, Material Collecting, Assembly, Testing, and Distribution. The development of this application involves the use of software such as Adobe Animate, Draw.io, and Balsamiq Mockups to produce interesting and interactive learning materials. This application is designed for grade VI students of elementary schools in Garut Regency. The results show that the developed interactive multimedia application is able to provide a more interesting and effective learning experience for students. Alpha and beta testing showed that this application functions well and is positively received by users. Thus, the application of interactive multimedia in learning wayang golek can be an effective solution to preserve this traditional art and increase the younger generation's interest in local culture.